Particle tracking at 4 K: the Fast Annihilation Cryogenic Tracking (FACT) detector for the AEgIS antimatter gravity experiment - Storey, James; Canali, C.; Aghion, S.; Ahlén, O.; Amsler, C.; Ariga, A.; Ariga, T.; Belov, A. S.; Bonomi, G.; Bräunig, Philippe; Bremer, J.; Brusa, R. S.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
The AEgIS experiment is an international collaboration with the main goal of performing the first direct measurement of the Earth's gravitational acceleration on antimatter. Critical to the success of AEgIS is the production of cold antihydrogen (H¯) atoms. The FACT detector is used to measure the production and temperature of the H¯ atoms and for establishing the formation of a H¯ beam. The operating requirements for this detector are very challenging: it must be able to identify each of the thousand or so annihilations in the 1ms period of pulsed H¯ production, operate at 4K inside a 1T solenoidal field and not produce more than 10W of heat. The FACT detector consists of two concentric cylindrical layers of 400 scintillator fibres with a 1mm diameter and a 0.6mm pitch. The scintillating fibres are coupled to clear fibres which transport the scintillation light to 800 silicon photomultipliers. Each silicon photomultiplier signal is connected to a linear amplifier and a fast discriminator, the outputs of which are sampled continuously by Field Programmable Gate Arrays (FPGAs). In the course of the developments for the FACT detector we have established the performance of scintillating fibres at 4K by means of a cosmic-ray tracker operating in a liquid helium cryostat. The FACT detector was installed in the AEgIS apparatus in December 2012 and will be used to study the H¯ formation when the low energy antiproton physics programs resume at CERN in the Summer of 2014. This paper presents the design requirements and construction methods of the FACT detector and provides the first results of the detector commissioning.
Available online 30 May 2013
Gesehen am 10.03.2022